4-[(Dimethylamino)methylidene]-2-(4-nitrophenyl)-1,3-oxazol-5(4H)-one - Romeiro, G.A.; Ribeiro, C.M.R.; Wardell, S.M.S.V.; Wardell, J.L.; Ng, S.W.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
The title molecule, C(12)H(11)N(3)O(4), is essentially planar, the r.m.s. deviation for all non-H atoms being 0.068 angstrom. An intramolecular C-H center dot center dot center dot N hydrogen bond occurs. The crystal packing is dominated by pi-pi interactions [shortest centroid-centroid distance = 3.6312 (16) angstrom], which lead to supra-molecular chains that are linked into a three-dimensional network via C-H center dot center dot center dot O contacts. The crystal was found to be a non-merohedral twin ( twin law -1 0 0/0 - 1 0/0.784 0 1), the fractional contribution of the minor component being approximately 22%.